Forest-fire interactions, impacts, and implications: a focus on mangroves - Dookie, Sabrina; Ansari, Abdullah Adil; Jaikishun, Sirpaul (New Zealand journal of forestry science, 2025)
Background: Fire plays a key role in the world’s wetland ecosystems, affecting the fundamental aspects of their ecological functioning. The increased frequency of wildfires continues to exert a significant influence on the succession of mangrove ecosystems and the spatial distribution of species. Numerous studies have attempted to highlight the effect of fires on forest ecosystem function and integrity; however, the results are inconclusive. In particular, it remains uncertain whether forest fires have direct impacts and implications on mangrove ecosystems, a forest type known for its distinct characteristics and low ignition rates due to high moisture levels. Methods: We have conducted a comprehensive review of over 120 relevant scholarly articles found through formal searches of literature and citation databases and by surveying relevant publications to identify and examine the interactions, prevalence, and implications of forest fires in mangrove ecosystems globally. We have also synthesised the impacts of recurrent fires on the numerous ecological goods and services offered by mangroves and highlighted the existing literature gaps and directions for future research. Results: Mangrove forest fires are prevalent in many countries across the world with varying distributions of forested areas. While there are numerous causes of wildfires in mangroves, most occurrences are due to a combination of natural dry periods (El Niño events) and anthropogenic activities, which may deliberately or accidentally increase fire regimes. There are many negative effects of mangrove forest fires which can affect the goods and services provided to the environment and society, including habitat loss, pollution, and wildlife destruction. However, our findings have highlighted some cases where wildfires have positive effects on mangrove ecosystems by encouraging nutrient enrichment and habitat expansion. Our review reports numerous literature gaps with high priorities for future research on understanding sustainable forest management with the coexistence of fires through preservation, conservation, and public awareness. Conclusions: Forest fires are prevalent in mangrove ecosystems due to a combination of natural phenomena and human-induced factors. With predominantly negative effects, forest fires result in a loss of ecological integrity, leading to severe economic losses and habitat degradation. Emphasis should therefore be placed on sustainable forestry and public awareness for the mitigation of the dynamic effects of forest fires on mangrove ecosystems.